Analysis of Purchase Intention for Halal-Certified Food Products Among Generation Z Consumers in South Tangerang City - Daman Sudarman; Nazifah Husainah; Dadang Dadang; Vita Nur (CV. Proaksara Global Transeduka, 2025)
Non-Muslim consumers are now showing increasing interest in halal food products, particularly due to perceptions of cleanliness, quality, and safety. This phenomenon is expanding the halal market, which was previously synonymous with Muslim consumers. This study aims to analyze the factors that influence the purchase intention of non-Muslim consumers toward packaged food products with halal logos. Using a quantitative approach with Structural Equation Modeling (SEM) based on Partial Least Square (PLS), this study examines the influence of variables such as subjective norm, perceived behavioral control, halal awareness, and halal logo on purchase intention, both directly and indirectly through attitude as a mediating variable. Data was collected from 300 non-Muslim respondents who had purchased halal-certified products in the Jakarta Capital Region. The results indicate that attitude has a significant influence on purchase intention and serves as an important mediating variable in the relationship between external factors and purchasing decisions. These findings contribute theoretically to the development of the Theory of Planned Behavior (TPB) model in the context of halal consumption by non-Muslims, as well as practical implications for halal food industry players in designing more inclusive marketing strategies.